(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
The aim of this research is to identify the degree of achieving equal educational opportunities in the Classes ready to go to school, where the descriptive analytical approach was used. The most important results were: The degree of achieving equal educational opportunities in the field of material equipment was medium, and in the areas of administrative services and educational services was high. There are no statistically significant differences between the mean scores of the responses of the study sample for the two domains (administrative services, educational services) according to the variable of school location, academic and educational qualification, and number of years of experience. City center and for the benefit of educational mentors.